The Brain Anatomy of the Brown Bear (Carnivora, Ursus arctos L., 1758) Compared to That of Other Carnivorans: A Cross-Sectional Study Using MRI - Sienkiewicz, Tomasz; Sergiel, Agnieszka; Huber, Djuro; Maślak, Robert; Wrzosek, Marcin; Podgórski, Przemysław; Reljić, Slaven; Paśko, Łukasz (Frontiers in Neuroanatomy, 2019)
In this study, we aimed to provide a neuroanatomy atlas derived from cross-sectional and magnetic resonance imaging (MRI) of the encephalon of the brown bear (Ursus arctos). A postmortem brain analysis using magnetic resonance imaging (MRI – 1,5T; a high-resolution submillimeter three-dimensional T1-3D FFE) and cross-sectional macroscopic anatomy methods revealed major embryological and anatomical subdivisions of the encephalon, including the ventricular system. Most of the internal structures were comparably identifiable in both methods. The tractus olfactorius medialis, corpus subthalamicum, brachium colliculi rostralis, fasciculus longitudinalis medialis, nuclei vestibulares, velum medullare rostrale, nucleus fastigii, fasciculi cuneatus et gracilis were identified entirely by cross-sectional macroscopic analysis. However, the glandula pinealis, lemniscus lateralis and nuclei rhaphe were visualized only with MRI. Gross neuroanatomic analysis provided information about sulci and gyri of the cerebral hemispheres, components of the vermis and cerebellar hemispheres, and relative size and morphology of constituents of the rhinencephalon and cerebellum constituents. Similarities and discrepancies in identification of structures provided by both methods, as well as hallmarks of the structures facilitating identification using these methods are discussed. Finally, we compare the brown bear encephalon with other carnivores and discuss most of the identified structures compared to those of the domestic dog, the domestic cat, Ursidae and Mustelidae families and Pinnipedia clade.